Interrelationships of Flour, Dough, and Bread Properties Under Reduced Salt Level Conditions. Issue 4 (27th March 2017) - Yovchev, Aleksandar; Briggs, Connie E.; Stone, Andrea K.; Scanlon, Martin G.; Tyler, Robert T.; Hucl, Pierre J.; Nickerson, Michael T.
Abstract : The interrelationships between flour quality and the variability in the dough physical properties and bread loaf characteristics were investigated under reduced salt conditions using partial least squares (PLS) regression analysis. Seventy‐two percent of the variability in dough physical properties was explained by the flour quality using a three‐factor PLS model. Damaged starch content (DS), protein content, and farinograph dough development time (DDT) explained the variability of dough creep‐recovery behavior along PLS‐1. Farinograph absorption (FAB), located along PLS‐2, was strongly related to dough adhesiveness, in which adhesiveness was highly correlated to dough stickiness ( r = 0.91). Eighty‐nine percent of the variability in bread loaf characteristics was explained by the flour quality using a four‐factor PLS model; the first two PLS factors explained 66% of the variability. The loaf volume was related to a high number of loaf cells, whose expansion resulted in a greater loaf height. The relation between loaf volume and loaf height was expressed more in PLS‐3 than PLS‐1 and PLS‐2. Mean cell wall thickness and mean cell diameter were closely related negatively along PLS‐1, for which DS and farinograph dough stability explained much of the variability in these loaf characteristics. Along the third PLS factor, FAB explained the variability in loaf weight.